Manipulation of Bioprocess in Rumen to Improve Fiber Feed Utilization - Puastuti, Wisri (Indonesian Animal Sciences Society, 2009)
Ruminant has a unique digestive organ that has big capacity to digest fiber. The digestive process includes the interaction of feed, rumen microbe and animal itself. Fementative digestion gives an advantage for ruminant as majority of feed consists of fiber, i.e: cellulose, hemi cellulose and xylan. Rumen microbes have an important role to digest fiber. Rumen microbes could be manipulated by several strategies to increase microbial protein synthesis and microbial activity. Feed supplement could stimulate growth and activity of rumen microbes, while buffer could stabilize the rumen pH and also the fermentation. Defaunating agent was given to control the existence of rumen microfauna (protozoa) so increase the population of bacteria. Essensial amino acid was used as a growth factor of rumen microbe the amino acid or its precursor could be given as supplementation. Feeding probiotic could maintain anaerob condition in the rumen, and caused population and activity of rumen microbe increased. Addition of micro mineral or enzyme could improve the fermentation and feed degradation in the rumen, hence, improved feed intake and animal productivity. Â Key words: Rumen microbe, fiber source, manipulation, digestion